Crystal structure of bis[μ-methoxy(pyridin-2-yl)methanolato-κ3N,O:O]bis[chloridocopper(II)] - Sujirat Boonlue; Anchalee Sirikulkajorn; Kittipong Chainok (Acta Crystallographica Section E: Crystallographic Communications, 2015)
The racemic title compound, [Cu2(C7H8NO2)2Cl2], is composed of dinuclear molecules in which methoxy(pyridin-2-yl)methanolate ligands bridge two symmetry-related CuII ions. Each CuII ion is coordinated in a square-planar geometry by one Cl atom, the N and O atoms of the bidentate ligand and the bridging O atom of the centrosymmetrically related bidentate ligand. The separation between the two CuII atoms is 3.005 (1) Å. In the crystal, non-classical C—H...O hydrogen bonds, weak π–π stacking [centroid–centroid distance = 4.073 (1) Å] and weak electrostatic Cu...Cl interactions [3.023 (1) Å] link the dinuclear molecules into chains running parallel to the b axis. These chains are further connected by weak C—H...Cl hydrogen bonds directed approximately along the a axis, forming a three-dimensional supramolecular network.